Economic sustainability of Spanish table grapes in different water and technology contexts - Fernández-Zamudio, María A.; Alcón, Francisco J.; Caballero, Pedro (2017)
Eighty-five percent of Spanish table grapes are produced near the Mediterranean Sea, in very and regions. The irrigation-water availability influences the cropping plans adopted on farms and, on the medium-term, it will also influence viability and competitiveness. This work is aimed at analysing the effects of the main technological improvements introduced on farms and determining the economic consequences, derived from other production scenarios characterized by variability in irrigation-water supply and price. Mathematical programming has been applied to models established for representative farms in Murcia and Alicante. After obtaining the most direct results of investment in technology, the modelization shows that the on-farm water availability exerts a greater effect than the water price, and that only technologically equipped farms can face increases in the price of this resource, keeping their economic sustainability constant.